Risk perception by food handlers in the tourism sector - Marcel Levy de Andrade; Gilma Lucazechi Sturion; Natalie Verónika Rondinel Mendoza (Fundação Oswaldo Cruz (FIOCRUZ), 2016)
The objective of this study was to evaluate the perception of risk by food handlers in the food services of the tourism sector. One structured methodological instrument was used to analyze the risk perception of 108 food handlers from 19 establishments in a tourist region in the State of São Paulo, Brazil. The highest score was related to the subject "Integrated pest control" and the lowest level was related to "Eating soft-cooked eggs". Differences (p < 0.05) were observed among the levels of risk perception, making it possible to form three sub-groups concerning the questions. The central topic of the first sub-group was safety aspects in food production (I), the second related to sanitation operations (II) and the third to integrated pest control (III). Sub-groups II and III presented the greatest level of perceived risk. Differences (p < 0.05) between the level of risk perception and the socio-demographic variables were identified. Women showed greater risk perception compared to men. The results can provide important information for public and private programs, improving development of institutional strategies directed at food safety.